Biomass yield, nutritional value and in vitro ruminal fermentation kinetics of Guatemala grass (Tripsacum laxum) at different harvesting stages and agro-ecologies in southern Ethiopia - Aba Jebel, Abdo (Jimma University, 2023)
The study was conducted to evaluate the effect of agro-ecologies and harvesting date on morphological traits, biomass yield, chemical composition, in vitro dry matter digestibility and in vitro ruminal fermentation kinetics of the Guatemala grass in southern Ethiopia. The experiment was laid out in a factorial arrangement of two agro-ecologies and three harvesting dates in a randomized complete block design (RCBD) with three replications. Data collection included morphological parameters, dry matter yield, chemical composition, and in vitro gas production. Data was analyzed using GLM procedure of SAS (SAS, 2014, Ver. 9.3). The results indicated that harvesting stage significantly (p<0.05) influenced morphological parameters whereas plant height (PH), Number of nodes per plant (NNPP) and dry matter yield (DMY) were tended to be affected by variations in agro-ecologies. Guatemala grass from mid- agro-ecologies yielded significantly higher (p<0.05) crude protein (CP) content and. The result also showed that delaying the harvesting stage led to an increase in fiber content, but insignificant (P>0.05) a decrease (P) in CP, ME, IVOMD. Guatemala grass harvested from mid agro-ecologies and early harvesting stage were significantly higher(P<0.05) in CP, IVOMD and ME. The proximate composition, nutritive value, IVOMD and gas production potential of forage grass showed great variability across different agro-ecologies and harvesting stages. During the incubation period, from 3 hours to 24 hours, gas production was notably higher (p<0.05) at grass harvested from lower agro-ecologies. In the first 3 and 6 hours of incubation, grass harvested at a later maturity stage produced a significantly higher (P <0.05)) volume of total gas. The production of gas from the degradable fraction (b) had a significant impact (p<0.05) on the total volume of gas throughout the incubation period and influenced methane emissions after 72 hours. Gas production from the potentially degradable fraction (b) significantly (p<0.05) affected the total gas volume throughout the incubation period and had significantly (p<0.05) influenced methane emission after 72hr. There was a strong and negative correlation between the CP content and NDF (r= -0.415), ADF (r= -0.170), and ADL (r= -0.559), while a strong positive correlation was observed between CP content and both IVOMD(r=0.802) and ME(r=0.710). Methane exhibited a strong positive correlation (r =517) with total gas production during the in vitro microbial fermentation process. Based on the morphological parameters and dry matter yield, Guatemala grass contains moderate quality to support ruminant production. However, this study was limited to one sampling season; therefore, further research is needed to explore the changes in chemical composition and nutritional values across different seasons.